DEIXIS ANALYSIS ON SONG LYRICS IN THE ALBUM OF THE BLACK PARADE BY MY CHEMICAL ROMANCE A PRAGMATICS STUDY - Murti Wardhani, Evi; Eka Febiyanti, Latifah (Universitas Duta Bangsa Surakarta, 2024)
This study focuse on a deixis analysis of theÂ lyrics of My Chemical Romance's album